Assessment of the temporal variation of electrical potential and pH of different bleaching agents - Pretel, Hermes [UNESP]; Lucas de Sousa Gomes Costa, Joatan [UNESP]; Esteban Florez, Fernando Luis; Nogueira, Básia Rabelo [UNESP]; Batista de Oliveira Junior, Osmir [UNESP] (Elsevier, 2021)
Introduction: Tooth whitening procedures are under continuous investigation to improve esthetic outcomes and reduce bleaching sensitivity (BS) precipitating from treatments. During the dental bleaching process it is known that the release of free radicals degrades the organic pigment molecules of the tooth and with this an amount of energy is released. Nonetheless, previous studies have never investigated the temporal correlation between of pH and electric potential (EP) generated in this treatment. Objectives: Therefore, the objective of the present study was to investigate temporal variations of pH and EP associated with three different commercially available bleaching gels and the correlation levels between parameters of interest to provide relevant information regarding the kinetics of oxidation reactions in dental bleaching procedures. Methods: The study was divided into 3 groups (n = 9) in function of hydrogen peroxide concentration (either 6%, 15% and 35%). The temporal evolution of pH and EP values were determined using a highly-accurate and previously calibrated pH meter at specific time-points (5, 10, 15 and 30 min). Results: Data obtained were submitted to one-way ANOVA of repeated measures with Bonferroni post-test (α = 0.05). The results of the study showed difference in the factor gel concentration (p < 0,0001), time (p < 0,0001) and interaction (gel/time) (p = 0.002) while throughout the intervals evaluated the groups remained relatively stable and without significant difference in the intragroup variation of pH (p < 0.05) and in EDP only with significant difference in the 5 min interval of the 35% concentration. A 2nd order polynomial relationship test showed high correlation levels. Conclusion: It can thus be concluded that there is a negative relationship between EP and pH variation in the different gel concentrations. Clinical significance: The findings of the present study suggest that bleaching gels of higher concentration may provoke BS that are more intense and durable due to significant electric depolarization of neuronal extensions of pulpal tissues.
Keywords: Dental bleaching; Electric potential; Hydrogen peroxide; pH; Temporal evolution